Review pada Pengaruh Sudut Kemiringan Atap terhadap Keluaran Energi Piezoelektrik pada Eksperimen Konversi Energi dari Tetesan Air Hujan menjadi Energi Listrik - Pandu Kusuma Pangestu; Rifky; Muhammad Fahmi Nurhidayat; Kurnia Sandi Oktaris; Reyhan Martin Firnanda; M. Rafi Cahya Firdaus (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
This review was conducted to examine the effect of variations in roof slope angles on the amount of piezoelectric energy generated from the impact of artificial rainwater. The study utilized a miniature roof model with four different slope angles: 15°, 30°, and 45°. Piezoelectric sensors were placed on the underside of the roof surface, which was made of polycarbonate material. Rain simulation was performed using a demonstration device with a constant water discharge rate and controlled droplet size. The voltage and electric current produced at each slope variation were measured using a multimeter. Each experiment was repeated three times to ensure the validity and consistency of the results. The collected data were analyzed to determine the relationship between the roof slope angle and the electrical output by presenting voltage and current graphs against the slope angle and calculating the energy conversion efficiency. The results showed that variations in the roof slope angle affected the generated piezoelectric energy, and an optimum angle was identified that produced the highest voltage and current.